Knowledge of Risk Factors and Warning Signs of Stroke among Hypertensive Patients at Jakaya Kikwete Cardiac Institute, Tanzania: A Cross-Sectional Study (Tanzania Medical Journal, 2025)
Background In Tanzania, approximately two-thirds of patients who die from stroke have a history of hypertension. Awareness of stroke risk factors and the ability to recognize its warning signs are critical, particularly among high-risk populations such as individuals with hypertension. However, there is limited evidence in Tanzania regarding the level of knowledge among hypertensive patients about these risk factors and early warning signs of stroke. Broad objectiveAssessment of knowledge of risk factors and warning signs of stroke among hypertensive patients at the Jakaya Kikwete Cardiac Institute in Tanzania.MethodsA descriptive cross-sectional survey was conducted between February and March 2022 among patients with hypertension attending clinic at the Jakaya Kikwete Cardiac Institute. A systematic sampling technique was used to recruit 280 study participants. Quantitative data were collected using an interviewer-administered questionnaire. Descriptive statistics and logistic regression analyses were performed using SPSS version 25.ResultsA total of 280 participants were included in this study. Among the study participants, only less than half of them had adequate knowledge of the risk factors (46.5%) and only half (40.6%) of them had adequate knowledge of warning signs of stroke. Urban residence (AOR 4.63; 95%CI 1.65-12.98) and tertiary education level (AOR 12.73; 95%CI 5.31-30.59) were associated with higher odds of having adequate knowledge of stroke risk factors. Tertiary education level (AOR 10.98; 95%CI 4.96-26.22) and previously seeing someone with a stroke (AOR 11.31; 95%CI 4.99-25.61) were associated with higher odds of having adequate knowledge of stroke warning signs.Conclusion and recommendationsThis study revealed that the majority of participants had inadequate knowledge of stroke risk factors and warning signs. Significant predictors of knowledge included education level, place of residence, and prior exposure to stroke. Therefore, targeted educational programs aimed at increasing stroke awareness among individuals with hypertension should be implemented, with particular emphasis on rural areas. Healthcare providers should ensure that hypertensive patients receive adequate and personalized information regarding their stroke risk and early warning signs.